Prolonged course of brain edema and neurological recovery in a translational model of decompressive craniectomy after closed head injury in mice - Szczygielski, Jacek; Hubertus, Vanessa; Kruchten, Eduard; Müller, Andreas; Albrecht, Lisa Franziska; Schwerdtfeger, Karsten; Oertel, Joachim (Frontiers in Neurology, 2023)
Background The use of decompressive craniectomy in traumatic brain injury (TBI) remains a matter of debate. According to the DECRA trial, craniectomy may have a negative impact on functional outcome, while the RescueICP trial revealed a positive effect of surgical decompression, which is evolving over time. This ambivalence of craniectomy has not been studied extensively in controlled laboratory experiments. Objective The goal of the current study was to investigate the prolonged effects of decompressive craniectomy (both positive and negative) in an animal model. Methods Male mice were assigned to the following groups: sham, decompressive craniectomy, TBI and TBI followed by craniectomy. The analysis of functional outcome was performed at time points 3d, 7d, 14d and 28d post trauma according to the Neurological Severity Score and Beam Balance Score. At the same time points, magnetic resonance imaging was performed, and brain edema was analyzed. Results Animals subjected to both trauma and craniectomy presented the exacerbation of the neurological impairment that was apparent mostly in the early course (up to 7d) after injury. Decompressive craniectomy also caused a significant increase in brain edema volume (initially cytotoxic with a secondary shift to vasogenic edema and gliosis). Notably, delayed edema plus gliosis appeared also after decompression even without preceding trauma. Conclusion In prolonged outcomes, craniectomy applied after closed head injury in mice aggravates posttraumatic brain edema, leading to additional functional impairment. This effect is, however, transient. Treatment options that reduce brain swelling after decompression may accelerate neurological recovery and should be explored in future experiments.